Reflection of Cultural Values Through Learning Based on Local Wisdom at SDN Bakaran Wetan 01 - Ika Oktavianti; Eva Banowati; Hamdan Tri Atmaja; Thriwaty Arsal (Universitas Negeri Semarang, 2021)
The high trust of the Bakaran Wetan village community in Nyai Ageng Bakaran and its heritage, makes this village rich in cultural values. To maintain these cultural values, children as generations of heirs of local culture need to be equipped with learning based on local wisdom. The purpose of this study is to explain the implementation of learning based on local wisdom at SDN Bakaran Wetan 01, and to explore the cultural values ​​reflected in learning based on local wisdom at SDN Bakaran Wetan 01. This study uses a qualitative approach. Data collection techniques using observation, interviews and documentation. The validity of the data using source triangulation techniques. Analysis of the data using a spiral of qualitative data analysis according to Creswell. The results showed that learning based on local wisdom at SDN Bakaran Wetan 01 was implemented in curricular and extracurricular activities. In curricular activities, local wisdom in the form of the folklore of Nyai Ageng Bakaran, petilasan of Nyai Ageng Bakaran, building houses using white bricks, Sumpah Serapah wells, Bakaran batik, tiger prawns, milkfish and various preparations, are used as sources and media for thematic learning and strengthening character education. In extracurricular activities, the implementation of learning leads the child to the practice of ketoprak Bakaran and karawitan. In conclusion, learning based on local wisdom at SDN Bakaran Wetan 01 had reflected the tangible and intangible values ​​of Bakaran's culture to direct children to identify and analyze local potentials and advantages.